Numerical braille module for learning simple mathematical operations - Mohd Tahir, Mohamad Safiddin; Mohamad Hanif, Noor Hazrin Hany; Md Yusuf, Hazlina (IEEE, 2020)
Individuals with a good understanding of mathematics have better chances to do well in their life. However, it is an extremely challenging task for people with visual disabilities to learn and execute simple mathematical operations. Although there are many mathematical learning products in the current market, most of them are expensive, with smooth input keys, liquid crystal display and audio outputs which limit the learning process of numerical braille code. In this paper, we present a numerical braille module which aimed to help people with visual challenges to learn simple mathematical operations. This module comprises 12 miniature solenoids that were controlled by an Arduino Uno microcontroller with a numeric keypad that serves as an input unit. The verification of input and output signals was conducted to ensure that all the inputs are correctly stored in Arduino board memory to perform a correct operation and raised the correct solenoids to produce a braille code pattern. Three operations were tested, which are addition, subtraction and multiplication. The developed numerical braille module was capable of performing simple calculations tasks and raised correct solenoid output accordingly. The outcome of this work provides an optimistic prospect of attracting the visually impaired to learn and perform mathematical operations.